TUMBUH KEMBANG ANAK USIA DINI PADA MASA PANDEMI COVID-19 DI JOMBANGAN DESA TERTEK KECAMATAN PARE KABUPATEN KEDIRI - Dodik Arso Wibowo; Muhammad Taukhid (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Children's golden age is from 0 to 6 years old. Children of this age are very sensitive to the stimuli of their environment, especially the knowledge and skills they acquire from their parents. The purpose of this study was to describe early childhood growth and development during the Covid-19 pandemic. In a study design used descriptively in 54 children aged 2 to 3 years, using a sample of 10 respondents identified by targeted sampling techniques, the study instrument consisted of the following items: used early detection screening for developmental abnormalities in children, including: Weight and height, developmental pre-screening questionnaire for children aged 24-36 months, hearing test, vision test. Ratings are based on percentage formulas and are interpreted quantitatively. Results showed that almost all respondents (90%) had normal nutrition and all (100%) had normal head circumference when it came to growth. From a development perspective, almost all respondents (80%) have corresponding standards. All respondents (100%) had a normal baseline hearing test. All respondents (100%) had a normal baseline for their vision of the test item. Several factors explain the emergence and development of early childhood during the Covid-19 pandemic, including gender, parental age, child age, parenting style, parental education level, number of siblings, and sources of information on child development. was affected by Parents are encouraged to provide insight into their child's nutritional needs and development so that their nutritional needs are met and age-appropriate development is possible. It not only increases motivation to be more active in stimulating, training and developing a child's psychomotor skills